Chaetoceros ceratosporum Diatomae in Feed Formula To Increase Growth and Post Larvae Immunity of Tiger Shrimp (Penaeus monodon Fab.) to Vibrio harveyi infection - Ekawati, Arning Wilujeng; Nursyam, Happy; Widjayanto, Edi; Marsoedi, Marsoedi (Graduate School, Universitas Brawijaya, 2013)
This experiment aims to determine the effect and the best dose of Chaetoceros ceratosporum diatomae utilization in feed formula for post larvae of tiger shrimp (Penaeus monodon Fab.) growth and immunity to Vibrio harveyi infection. This research applied Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatment use Chaetoceros ceratosporum diatomae in feed formula (iso protein 39.02% and iso energy 3.58 kcal/g diet) in different doses, i.e. treatment A = 0 %; B = 3.04 %; C = 6.0 8%; D = 9.12 %. Observed parameters were Survival Rate, Growth Rate, Food Conversion Ratio (FCR) and Protein Efficiency Ratio (PER). Result showed that Chaetoceros ceratosporum diatomae utilization in feed formula affect the increase of growth and immunity of post larvae of tiger shrimp (Penaeus monodon Fab.) to Vibrio harveyi infection. The best dose in feed formula ranged from 5,75% - 5,95%. Key words: Chaetoceros ceratosporum, balance energy, feed conversion, protein efficiency, Vibrio harveyi, tiger shrimp